2016
DOI: 10.1176/appi.focus.140301
|View full text |Cite
|
Sign up to set email alerts
|

Impact of Adverse Childhood Experiences on Psychotic-Like Symptoms and Stress Reactivity in Daily Life in Nonclinical Young Adults

Abstract: Background

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 60 publications
0
2
0
Order By: Relevance
“…As affective disturbances mediate the effect of daily hassles on psychotic experiences, an affective pathway to psychosis has been proposed. In line with this, ESM studies have shown that exposure to social adversity, such as childhood trauma and major life events, is associated with increased reactivity even to minor stressors in daily life, suggesting a process of behavioural sensitization. In addition, these traumatic experiences were also linked to stronger psychotic reactivity to threat anticipation in daily life in individuals at the more severe end of the psychosis continuum.…”
Section: Applications Of Esm In the Mental Health Research Fieldmentioning
confidence: 93%
“…As affective disturbances mediate the effect of daily hassles on psychotic experiences, an affective pathway to psychosis has been proposed. In line with this, ESM studies have shown that exposure to social adversity, such as childhood trauma and major life events, is associated with increased reactivity even to minor stressors in daily life, suggesting a process of behavioural sensitization. In addition, these traumatic experiences were also linked to stronger psychotic reactivity to threat anticipation in daily life in individuals at the more severe end of the psychosis continuum.…”
Section: Applications Of Esm In the Mental Health Research Fieldmentioning
confidence: 93%
“…To date, however, only one study has reported elevated stress sensitivity in a non-clinical sample of young adults exposed to bullying [41] and, to the best of our knowledge, no study has investigated the impact of bullying victimization on individuals' affective and psychotic reactivity to stress in a sample of help-seeking youth and whether effects of bullying exposure on stress sensitivity differ across individuals at differing liability to mental health conditions. To address current knowledge gaps, a sample of adolescents and young adults receiving help from a secondary mental health service (service users), their biological siblings, and controls were recruited in the current study.…”
Section: Introductionmentioning
confidence: 99%